The Evolution of Intertemporal Preferences - Robson, Arthur J; Samuelson, Larry (American Economic Review, 2007)
Where do preferences come from? What determines their properties? Though traditionally reluctant to ask such questions, economists have recently turned to evolutionary models for answers. We focus on intertemporal preferences here, arising out of the evolutionary implications of different reproductive strategies or life histories. An agent’s life history specifies the agent’s number and timing (and in a richer model, quality) of offspring. Evolution will select the life history that maximizes the growth rate of the associated group of individuals. We begin with the simplest possible biological life history, that of a semelparous agent that, if it survives a fixed number of years, reproduces and then dies. We show the evolutionary criterion for success in this case entails hyperbolic time discounting of the log of the number of offspring produced. The rate of time preference is a function of age, however, not of time relative to the present, and there are no preference reversals in the sense of behavioral economics. At the same time, the optimal strategy maximizes the exponentially discounted number of offspring, provided we discount at the sum of the death rate and the maximal growth rate. Conventional discounting thus suffices to induce optimal choices from the agent. More generally, if the animal is iteroparous, that is, has a nondegenerate profile of offspring, we show the evolutionary indifference curves over offspring of various ages are hyperplanes that are not parallel, but tilt to reflect greater impatience as the growth rate increases. There is no additively separable function of the age profile of expected offspring that is globally equivalent to this basic biological growth-rate The Evolution of Intertemporal Preferences